Sport as an actor of big politics: Football and its social function - Biljana Prodović Milojković (Exercise and Quality of Life)
The author finds the reason for writing the paper in the current holding of the World Football Championship in Qatar, as one of the biggest sporting events bigger and more significant than the Olympic Games themselves. Often this great global event is seen as the last place where the small can defeat the big, thereby losing the illusion that the rich and the big always win, and that “David can beat Goliath”. Taking the facts into account, football is still primarily a game of the poor, in which the largest number of footballers came from the margins which, according to the author, reflects its greatest social strength. In his work, the author intends to describe and explain the world in which we live through the prism of not only previous championships. It is through the metaphor of football that the author deals with the issue of global order, with the fact that the main issues of this work are more cultural than economic. As the work is of a theoretical nature, the author's intention is to devote special attention to the consideration of physical culture and sport as a factor of socialization within this theoretical analysis, with a special emphasis on the sociology of football.